Modelling of PID speed control based collision avoidance system - L. M., Keong; Ahmad Shahir, Jamaludin; M. N. M., Razali; A. N. S. Z., Abidin; M. R. M., Yasin (Penerbit UMP, 2020)
To date, motor vehicle collisionsin Malaysia is still considerably high particularlyduring festiveseasons. These collisions may have been contributed by various factors viz road users, the vehicles or due to the road design. To reduce the possibilities of vehicle collisions, vehicle manufacturers have incorporate various types of active safety features as part of their vehicle specifications. However, cost seems to be a continous matter of argument among the industries, authorities and consumers.To ensure the sustanability and practicality of such features, it is necessary to develop a low cost yethigh effectiveness collision avoidance system that is affordable inevery vehicles. Therefore, this research focusesin designingand modellingalow costcollision avoidance system that will decelerate vehicles when approaching on-road obstacles. The effectiveness of this collision avoidance system is evaluated based on its effectiveness inslowing down vehicles when the system detectsobstacles in front, similar to the Autonomous Emergency Braking (AEB) features in vehicles which has now becoming more and more common for new models. In this research, the collision avoidance system will be tested on a model car that is built with robot car chassis. The Arduino Nano acts asthe controller for the system while ultrasonic sensorsand encoder sensors are used to detect the distanceofobstaclesand speed of the wheelsrespectively. The Arduino board isprogrammed with PID control algorithm to allow the model car to decelerate when approaching obstacle and come to complete stop before colliding with the obstacles. According to the result obtained, the most suitable PID constants for this collision avoidance system is Kp = 0.7, Ki = 0.7 and Kd = 0.07. The collision avoidance system is sensitive to sudden obstaclesas it can stop the model car within0.3 second from obstacledetection.To conclude, this system can effectively avoid the model car fromcrashing into the front obstacle thus may be beneficial as reference for low cost collision avoidance technologies for commercial purposes in motor vehicle technologies.